Coordinated care versus standard care in hospital admissions of people with chronic illness: a randomised controlled trial. Issue 1 (6th July 2015) - Plant, Natalie A; Kelly, Patrick J; Leeder, Stephen R; D'Souza, Mario; Mallitt, Kylie‐Ann; Usherwood, Tim; Jan, Stephen; Boyages, Steven C; Essue, Beverley M; McNab, Justin; Gillespie, James A
Abstract: Objective: To determine whether Care Navigation (CN), a nurse‐led hospital‐based coordinated care intervention, reduced the use of hospital services and improved quality of life for patients with chronic illness. Design: Randomised controlled trial; participants were allocated to CN or standard care. Participants and setting : Patients with chronic illness presenting to the emergency department of Nepean Hospital, Sydney, New South Wales. High‐risk status for an unplanned admission was defined as i) three or more unplanned hospital admissions in 12 months for patients aged ≥ 70 or at least one admission for cardiac or respiratory disease in patients aged 16–69 years; or ii) judged by a CN nurse to be high risk and likely to benefit. Main outcome measures: Numbers of re‐presentations or readmissions, quality of life, time to re‐presentation, readmission or death, length of stay, and access to hospital and community health services. Results: 500 participants were randomised between May 2010 and February 2011; 359 by previous unplanned admission and 141 by clinical impression. The CN group received more community health services (rate ratio, 1.94; 95% CI, 1.35–2.81; P < 0.001) than participants receiving standard care; however, this did not result in statistically significant differences in number of re‐presentations (rate ratio, 0.83; 95% CI, 0.68–1.01; P = 0.07), number of readmissions (rate ratio, 0.85; 95% CI, 0.70–1.04; P = 0.11), quality of life at 24 months (mean difference, 0; 95% CI, − 0.10 to 0.09, P = 0.93), or other measures. Conclusions: CN did not improve quality of life or reduce unplanned hospital presentations or admissions despite community health services almost doubling. Future service development should explore potential benefits of linking navigated intrahospital care to ongoing, proactive care planning and delivery in the community. Trial registration: ACTRN12609000554268.